Conjugates of modified hyaluronic acid with amino compounds for biomedical applications - Buffa, Radovan; Odstrčilová, Lucie; Šedová, Petra; Basarabová, Ivana; Novotný, Jaroslav; Velebný, Vladimír (Carbohydrate polymers, 2018)
Hyaluronic acid (HA) modified with an aldehyde group (HA-CHO) has enormous potential for the covalent attachment of the amino compounds and for the crosslinking of HA with bis or multi-functional amino linkers under physiological conditions. Modification of HA-CHO to its α,β-unsaturated analogue (ΔHA-CHO) generally increases the stability of the reversible imino-attachment due to conjugation of the imine moiety with the adjacent CC double bound. Conjugation of a wide range of structurally different amines including the amines with enhanced biological activity were studied in detail. Results showed that the stabilities of the final conjugates ΔHACHNR significantly depend on the chemical structure of the amine and on the pH value.
Keywords: Hyaluronan; koncentrace vodíkových iontů; Imine; kyselina hyaluronová; Conjugate; aminy; Unsaturated; pH-responsivity; Hydrogen-Ion Concentration; Aldehydes; Hyaluronic Acid; Aldehyde; Amines; aldehydy